PERAN SUB BIDANG PENDIDIKAN DAN PELATIHAN BKD - Dian Lestari, Tanti; Hasan Afandi, Ahmad; Muhaimin, Hikmah (MAJAPAHIT POLICY, 2023)
This research aims to describe the role of the BKD education and training sub-sector in increasing apparatus resourcesMojokerto city government. role is a form of behavior expected from someone in a particular social situation, while roleis a dynamic aspect of position, for example if someone carries out their rights and obligations in accordance with their position, then pThis means carrying out a role. concept from Max Weber, namely the Ideal Type of Rational Bureaucracy using descriptive research methodsQualitative research results explain that in carrying out its role, the Education and Training Sub-Sector has the role of compiling a List of NeedsAdvanced Training and Functional Technical Training, Inventory data on prospective participants in Advanced Training and Functional Technical Training, Proposeparticipants in Advanced Training and Functional Technical Training, Proposing certification participants according to their field of expertise and functional technical participants,coordinating and collaborating in the implementation of training. The Education and Training Sub Bid has an output of 63 participants who took part in the PBJ Training, after the participants took partThe training, Training Sub Sector, had an outcome of 23 participants who successfully passed according to their abilities and expertise. 23 participantsbecome an ASN who is ready to fill the positions needed by the government. Looking at the percentage, 23 participants out of 63 participants is definitely still far fromexpectations of the Education and Training Sub Sector. Then the budget for implementing the training is also quite large, thus affecting credibilityMojokerto City government